TINJAUAN FARMAKOTERAPI IKTIOSIS LAMELARIS (IL): LAPORAN KASUS - Riki Nova (Nusantara Hasana Journal, 2023)
Ichthyosis is a group of various inherited and acquired keratinizing diseases with generalized scaling characteristics. Lamellar ichthyosis (IL) lasts a lifetime and almost always involves the entire skin surface. The diagnosis of IL in this patient is based on anamnesis history of premature birth covered in collodion membrane all over the body, physical examination for the presence of all-over sheet-like scales, slight erythema and fissures, family history, skin biopsy and laboratory findings for analysis of gene mutations. In this case of IL, pharmacological management, namely topical administration, in the form of albumin Vaseline as hydration after bathing is very useful for skin with ichthyosis; administration of tretinoin (0.025-0.05%) is an irritating keratolytic after several applications showing better skin barrier but can cause very painful fissures; and the use of antiseptics, eg antibacterial soaps, chlorhexidine, or iodine can help control bacterial colonization.